Peranan E-Service Quality, Rates Dan Customer Trust Bagi Repurchase Intention Jasa Kurir - Amirah Kamila Safitri; Mohamad Rizan; Rahmi (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
The main objective of this study is to find out the direct and indirect effects of e-service quality and rates on repurchase intention with customer trust as the mediation. The research sample consisted of 250 respondents collected through the distribution of questionnaires. The data processing software employed is SPSS and LISREL 8.8 for the Structural Equation Model (SEM) method. The research sample consisted of 250 respondents, collected by distributing questionnaires online. Additionally, e-service quality together with rates also have a significant and positive effect on repurchase intention, both with or without the mediating role of customer trust. Furthermore, customer trust also has a significant and positive influence on repurchase intention. Therefore, if a courier service company aims to enhance repurchase intention, it needs to improve the quality of electronic services provided and offer competitive rates to customers. This will foster trust and boost the likelihood of repeat purchases.